(untitled) (Texas Journal of Philology, Culture and History, 2023)
National-cultural analysis of the names of ceremonial dishes in the system of the Uzbek gastronomic lexicon - the development of the national, cultural and socio-political consciousness of the Uzbek people, the formation of the outlook and thinking of young generation, and exploring the moralaesthetic and spiritual-meaning of the society plays an important role on this study. The purpose of this research work is to analyze the names of ceremonial dishes in the system of Uzbek gastronomic lexicon from a national-cultural point of view, to clarify their semantics; It consists of identifying, describing and classifying ritual foods related to people’s culture, values, customs, traditions, and social relations, and on this basis determining the linguistic value of ritual foods.